1993
DOI: 10.1111/j.1600-0609.1993.tb00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serum lactic dehydrogenase levels and fraction of S‐phase cells in non‐Hodgkin lymphomas

Abstract: Sixty‐four untreated patients with non‐Hodgkin lymphomas (NHL) were analyzed with respect to fraction of S‐phase cells in tumor material and serum lactic dehydrogenase (LD) levels. A significant correlation between the two variables was found in the low‐grade (LGM) (r = 0.44, p<0.01), but not in the high‐grade (HGM) lymphomas. Shorter survival times were found for patients with tumors showing a high fraction of S‐phase cells (>4%) (p < 0.001) as well as for patients with elevated LD values (≥ 7.5 μkat/l) (p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…A negative correlation was demonstrated between pretreatment serum LD and the probability of survival in these patients [46]. A negative correlation was demonstrated between pretreatment serum LD and the probability of survival in these patients [46].…”
Section: Oncologymentioning
confidence: 79%
“…A negative correlation was demonstrated between pretreatment serum LD and the probability of survival in these patients [46]. A negative correlation was demonstrated between pretreatment serum LD and the probability of survival in these patients [46].…”
Section: Oncologymentioning
confidence: 79%
“…The relevance of these B symptoms in patients with non-Hodgkin's lymphoma is less clear, but the symptoms tend to be related to more widespread or higher histological grade disease. Several previous large scale studies showed that hypoalbuminemia, elevation of serum β2 microglobulin (39,40) and an elevated LDH level were important prognostic factors for lymphoma with a FUO (41,42). Increased alkaline phosphatase activity can be an indirect indicator of progression and a poor prognosis of lymphoma (43).…”
Section: Discussionmentioning
confidence: 99%
“…Neither treatment response nor the survival time was impacted by LDH levels [19]. Other studies showed that serum LDH in cases of NHL and paediatric HD is considered as an important prognostic factor [20,21]. According to [19], increased activities of LDH reflected poor treatment prognosis, and it is considered the single parameter that has an independent prognostic importance.…”
Section: Ldh and Lymphomamentioning
confidence: 99%